Northward Shift of the Northern Hemisphere Westerlies in the Early to Late Miocene and Its Links to Tibetan Uplift. Issue 18 (23rd September 2022) - Tang, Yi; Wan, Shiming; Clift, Peter D.; Zhao, Debo; Xu, Zhaokai; Zhang, Jin; Song, Zehua; Jin, Hualong; Li, Mengjun; Shi, Xuefa; Li, Anchun
Abstract: Despite the importance of the westerlies to the global climate system, we still know little about their long‐term evolution and possible orographic controls during the late Cenozoic because of the lack of sedimentary records with precise chronological control. Eolian deposition in the North Pacific preserved past information about the westerlies, the major wind system delivering Asian dust to the Pacific. A continuous, high‐resolution eolian flux record since 23 Ma was reconstructed from sediments at Deep Sea Drilling Project Site 296 in the North Pacific. Combined with dust flux at Ocean Drilling Program Site 1208, variations in their difference indicated a northwards shift of the westerlies during 23‒9 Ma and a relatively stable state since then. We suggest that Tibetan uplift since the early Miocene began to drive the poleward shift of the westerlies until 9 Ma, after which the westerlies remained relatively stable over Asia on million‐year timescales. Plain Language Summary: The Northern Hemisphere Westerly wind is a significant component of planetary‐scale atmospheric circulation and has a large impact on regional and global climate change. Although numerous modern observations and orbital time‐scale studies of the Westerly wind have been conducted, we still know little about its evolution on million‐year time‐scales, which may modulate the overall amplitude of short‐term variations. Eolian deposition in the North Pacific has preserved precious information about the westerlies in the past. A continuous and high resolution eolian flux record dating from 23 Ma was reconstructed from sediments at Deep Sea Drilling Project Site 296 in the Northwest Pacific. Combined with dust records at Ocean Drilling Program Site 1208 to the east, we constrain how the path and strength of the Northern Hemisphere Westerlies have changed since the early Miocene. The two eolian records indicate a northwards shift of the westerlies between 23 and 9 Ma and a relatively stable state since then. We suggest that stepwise uplift of the Tibetan Plateau since at least the early Miocene began to drive the northwards shift of the Northern Hemisphere Westerlies until about 9 Ma, after which the westerlies remained relatively stable over Asia‐North Pacific on million‐year timescales. Key Points: We reconstruct the eolian flux record in the North Pacific since 23 Ma at high resolution The Northern Hemisphere Westerlies shifted northward between 23 and 9 Ma and have remained relatively stable since then Tibetan uplift drove the northward shift of Northern Hemisphere Westerlies in the early late Miocene